Methods and technologies for adaptation of main and auxiliary equipment of compressor plants and stations to unstable operating conditions - A. D. Vanyashov; V. L. Yusha (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The hierarchical structure of the compressor industry facilities is presented, taking into account their interaction and mutual influence. Analysis of production facilities that implement the gas compression technology, unstable operating conditions, the cause and nature of their occurrence, the degree of influence on the impact on facilities of different levels was performed. The technologies of adaptation of compressor equipment to unstable operating conditions are systematized, at the same time, depending on the emerging tasks, adaptation technologies are divided into stages (levels) of implementation. Present problems of scientific and methodological nature on implementation of technologies of adaptation of compressor equipment to unstable operating conditions at different levels of hierarchical structure of facilities are shown.